Cyberslacking and Task Performance: Does Locus of Control Act as a Psychological Mediator? - Udik Jatmiko; Ahmad Jauhari (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study seeks to investigate the influence of cyberslacking on task performance, with locus of control serving as a mediating variable among Professional Village Assistants in Nganjuk Regency. A quantitative approach with a survey design was employed, involving 73 respondents. Data analysis was conducted using non-parametric statistical techniques, with hypothesis testing performed through Smart-PLS. The findings reveal that cyberslacking has a negative effect on locus of control, yet it does not have a significant impact on task performance. Furthermore, locus of control is not found to mediate the relationship between cyberslacking and task performance. These results indicate that cyberslacking does not directly lead to a significant decline in work performance, while strengthening locus of control may improve individuals’ capacity to regulate their performance. This study offers practical implications for organizational policy development aimed at enhancing the productivity of village assistants by minimizing the adverse effects of cyberslacking through reinforcing locus of control.